EMERGING TRENDS OF CYBER CRIME IN INDIA : A CONTEMPORARY REVIEW - Tanya Gupta (Universitas Internasional Batam, 2023)
The world has become more advanced in communication, especially after the invention of the internet. The 21st century has been characterized by massive technological innovations that have shaped the way people interact. The social, political, and economic dimensions of human life are facilitated by a digital age that has encompassed the whole world. Universally, there has been a rapid rise in the use of computers and electronic gadgets. These developments have led to significant growth in criminality, especially in cyberspace. Cybercrimes have grown progressively with perpetrators developing newer and sophisticated techniques every day. Despite the measures taken by the international community to combat the vice and mitigate its effects, cybercrimes have continued to rise alarmingly across the world. According to Cyber Security Breaches Survey of 2022, 39% of businesses worldwide have been a victim of cybercrime.[1]. In this paper, the author intends to give a brief account of historical background and evolution of cyber crime. This paper focuses that what are the types of cyber crime and provisions covered under Information and Technology Act, 2000 (IT Act). The author also tries to cover that how does number of cases related to cyber crime in India has been increasing day by day. This paper also focuses on the impact of cybercrime and what are the challenges faced during investigation and what will be the safety measures against cyber crime. In this paper, researcher intends to use the secondary data for illustrating the research paper to clarify certain cybercrimes and issues related to the Investigation and the impact of cyber crime. Keywords: Internet, cybercrime, IT Act, Impact and Challenges [1]Department for Digital, Culture, Media & Sport, UK Government, Security Breaches Survey, 2022 https://www.gov.uk/government/statistics/cyber-security-breaches-survey-2022/cyber-security-breaches-survey-2022 The world has become more advanced in communication, especially after the invention of the internet. The 21st century has been characterized by massive technological innovations that have shaped the way people interact. The social, political, and economic dimensions of human life are facilitated by a digital age that has encompassed the whole world. Universally, there has been a rapid rise in the use of computers and electronic gadgets. These developments have led to significant growth in criminality, especially in cyberspace. Cybercrimes have grown progressively with perpetrators developing newer and sophisticated techniques every day. Despite the measures taken by the international community to combat the vice and mitigate its effects, cybercrimes have continued to rise alarmingly across the world. According to Cyber Security Breaches Survey of 2022, 39% of businesses worldwide have been a victim of cybercrime.[1]. In this paper, the author intends to give a brief account of historical background and evolution of cyber crime. This paper focuses that what are the types of cyber crime and provisions covered under Information and Technology Act, 2000 (IT Act). The author also tries to cover that how does number of cases related to cyber crime in India has been increasing day by day. This paper also focuses on the impact of cybercrime and what are the challenges faced during investigation and what will be the safety measures against cyber crime. In this paper, researcher intends to use the secondary data for illustrating the research paper to clarify certain cybercrimes and issues related to the Investigation and the impact of cyber crime. [1]Department for Digital, Culture, Media & Sport, UK Government, Security Breaches Survey, 2022 https://www.gov.uk/government/statistics/cyber-security-breaches-survey-2022/cyber-security-breaches-survey-2022